2019
DOI: 10.1097/nnr.0000000000000349
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Adverse Childhood Experiences, Family Strengths, and Chronic Stress in Children

Abstract: Background: Researchers have demonstrated that maternal adverse childhood experiences (ACEs), such as abuse and neglect, are associated with prenatal risk factors and poor infant development. However, associations with child physiologic and health outcomes, including biomarkers of chronic or "toxic" stress, have not yet been explored. Objectives: The purpose of this study was to examine associations among past maternal experiences, current maternal posttraumatic stress disorder (PTSD) symptoms, and children's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 42 publications
2
33
1
Order By: Relevance
“…In addition, we are following the cohort described here longitudinally in order to look for longer lasting and potentially intergenerational effects of this early intensive intervention on both behavioral and biological systems. A follow-up study of the MTB control group revealed evidence of intergenerational transmission of toxic stress (Condon et al, in press); these findings will be compared with outcomes in MTB intervention families in future analyses. Efforts are under way to conduct a cost-analysis of MTB from both Phase 1 and 2 reports, as well as the documented differences in rates of obesity and overweight in MTB toddlers (Ordway et al, 2018), and later prevalence of maternally reported behavior problems (Ordway et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we are following the cohort described here longitudinally in order to look for longer lasting and potentially intergenerational effects of this early intensive intervention on both behavioral and biological systems. A follow-up study of the MTB control group revealed evidence of intergenerational transmission of toxic stress (Condon et al, in press); these findings will be compared with outcomes in MTB intervention families in future analyses. Efforts are under way to conduct a cost-analysis of MTB from both Phase 1 and 2 reports, as well as the documented differences in rates of obesity and overweight in MTB toddlers (Ordway et al, 2018), and later prevalence of maternally reported behavior problems (Ordway et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A review of these studies demonstrated that parents who experienced ACEs were more likely to have children with internalizing and externalizing problems. Parental experiences of abuse and neglect were associated with children's emotional problems and disruptive behavior (Babcock Fenerci et al, 2016;Condon et al, 2019;Cooke et al, 2019;Esteves et al, 2017;Letourneau et al, 2019;Madigan et al, 2015;McDonald et al, 2019;Plant et al, 2013;Plant et al, 2017;Roberts et al, 2004;Schickedanz et al, 2018;van de Ven et al, 2020). In the only study of this review that collected data from both mothers and fathers, it was revealed that maternal ACEs had a stronger relationship with child psychopathology than paternal ACEs.…”
Section: Direct Associations Between Parental Aces and Child Psychopathologymentioning
confidence: 99%
“…Mothers who faced more adversity in their own childhoods are more likely to use corporal punishment and to display hostile, intrusive, or frightening parenting behaviors ( Jacobvitz et al, 2006 ; Chung et al, 2009 ). Condon et al (2019) suggest that mothers who experienced high levels of adversity and stress early in life may have limited lived experiences to draw from in order to offer their children solace from stressful experiences or teach effective coping skills in the presence of current stressors. Intrusive, withdrawing or hostile parenting styles can have direct effects on the infant and young child, as well as contribute to challenges within the mother–child relationship ( Lyons-Ruth, 1996 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that maternal childhood trauma leads to disturbed caregiving behavior which in turn interferes with infants developing a secure attachment ( Lyons-Ruth and Block, 1996 ). Furthermore, a mother’s history of ACEs predicts higher behavioral problems and blood pressure levels – a tangible biomarker of stress – in children ( Condon et al, 2019 ). Nevertheless, the impact of maternal childhood adversity and toxic stress on parenting behaviors and child outcomes is probabilistic rather than deterministic.…”
Section: Introductionmentioning
confidence: 99%